Implication of fitrah based education in social studies learning (A case study at Sekolah Alam Yogyakarta) - Liviani, Ratna; Erawati, Muna; Rasimin, Rasimin; Thoriquttyas, Titis (Universitas Negeri Malang, 2023)
Fitrah-based education is a conscious effort to increase all the potential that God has given to humans so that they become humans who unite with God and can benefit other humans for the sake of a better civilization. This research aims to determine the implications of nature-based education contained in social studies learning. This research a qualitative descriptive method with interviews, observation, and documentation. Based on research results it is that education must be able to develop and improve human nature which has been bestowed by God since humans were born. Sekolah Alam Yogyakarta offers natural education based on fitrah. The implications applied to social studies learning at Yogyakarta Nature School include social interaction in society, understanding of nationality, diversity of Indonesian culture, and activities related to nature so that through these activities’ students’ nature can be improved. This requires support from family and society to improve the nature of students.